Problematic Smartphone Use in Adolescents: Are Parents’ Digital Competence, Parents’ Negative Attitudes, and Perceived Parental Efficacy Important? - Arsy Amaryllis Almatin; Shally Novita; Fitri Ariyanti Abidin (Journal of Educational, Health and Community Psychology, 2023)
The present study investigates whether parents' digital competence, parents' negative attitudes toward smartphones, and perceived parental efficacy of smartphones predict problematic smartphone use in adolescents. An online survey provided quantitative data from 102 participants. They were 63 mothers, and 39 fathers were involved in the study. Problematic smartphone use in adolescents was perceived by parents using the Problematic Media Use Measure. Parents’ digital competence was measured using Digital Competence Instrument. The Parental Perceptions of Technology Scale measured parents’ negative attitudes towards smartphones and perceived parental efficacy. All measurements were validated in the Indonesian version. Multiple linear regression analysis was used to analyze the data.